EFFECTIVENESS OF THE MONOPOLY MEDIA INDONESIAN CULTURE (MOBUSAN) ON THE UNDERSTANDING SOCIAL STUDIES CONCEPTS IN GRADE IV STUDENTS - Shofa, Iramaya; Santoso; Denni Agung Santoso (Indonesian Journal of Educational Development (IJED), 2025)
This research is based on students' lack of understanding of Indonesian culture. This is because along with the development of modern times and the influx of foreign culture which can be accessed easily via gadgets with an internet network, it makes students feel more interesting than their own national culture. Based on this, this research aims to determine the effectiveness of using Indonesian cultural monopoly media (MOBUSAN) on the ability to understand cultural concepts of class IV students at SD 5 Kandangmas. This research used a quantitative method with a pre-experimental design, one group pretest-posttest and the sample used was 17 students in class IV of SD 5 Kandangmas. The data collection techniques used consisted of interviews, observation, documentation, tests and questionnaires. The data analysis used is descriptive data analysis which includes the normality test and the paired sample t-test. The results obtained show an increase in students' understanding of cultural concepts. This can be seen from the paired sample t-test with a sig value. (2-tailed) = 0.000 < 0.05 then H0 is rejected and Ha is accepted. The conclusion is that there is an increase in the use of Indonesian cultural monopoly media (MOBUSAN) in understanding cultural concepts in class IV students at SD 5 Kandangmas.